Floyd, Smith & Co. letterbook - Floyd, Smith & Co.
Letterbook documenting the company's business activities. Includes references to congressional debates on the tariff and national bank legislation.
Company engaged in mercantile trade in Georgetown (Washington, D.C.).
Collection material in English.
Keywords: Merchants -- Washington (D.C.); National banks (United States); Tariff; Georgetown (Washington, D.C.) -- Commerce; United States -- Economic policy -- To 1933.